2018
DOI: 10.18632/oncotarget.25448
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant attenuation of HMG-CoA reductase expression potentiates the cancer cell growth-inhibitory effect of statins and expands their efficacy in tumor cells with epithelial characteristics

Abstract: HMG-CoA reductase (HMGCR) inhibitors, statins, are potent cholesterol reducing drugs that exhibit anti-tumor effects in vitro and in animal models, including attenuation of metastasis formation, and their use correlates with reduced cancer-specific mortality in retrospective human cohort studies. However, E-cadherin expressing epithelial- and mixed epithelial-mesenchymal cancer cell lines (reflective of primary and outgrowing metastatic tumor cells, respectively) require higher statin concentrations than mesen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 53 publications
4
13
0
Order By: Relevance
“…Upregulation of genes involved in cholesterol biosynthesis and HMGCR as a mechanism of cells’ resistance was confirmed and extended also by another study. It was shown 58 that the downregulation of HMGCR expression by siRNA in epithelial and mixed epithelial-mesenchymal cells improved cells’ sensitivity to atorvastatin’s growth inhibitory effect. That effect is mainly associated with blockade of isoprenoid synthesis.…”
Section: Statins and Mechanisms Of Resistancementioning
confidence: 99%
“…Upregulation of genes involved in cholesterol biosynthesis and HMGCR as a mechanism of cells’ resistance was confirmed and extended also by another study. It was shown 58 that the downregulation of HMGCR expression by siRNA in epithelial and mixed epithelial-mesenchymal cells improved cells’ sensitivity to atorvastatin’s growth inhibitory effect. That effect is mainly associated with blockade of isoprenoid synthesis.…”
Section: Statins and Mechanisms Of Resistancementioning
confidence: 99%
“…Sánchez et al [47] highlighted the antiproliferative effect of HMGCR inhibitors atorvastatin, fluvastatin and simvastatin on MCF-7 breast cancer cells; This effect was associated with a decrease in DNA synthesis and cell cycle arrest in the G1 and G2/M phases. A recent study of Ishikawa et al [48] has shown that HMGCR inhibitor statin inhibits the proliferation and migration of cancer cells, as well as the formation of metastases. The effect of 4-cholesten-3-one on HMGCR expression was examined in MCF-7 and MDA-MB-231 cells and a decrease in mRNA expression was observed, suggesting that cholesterol synthesis was downregulated in our cell models treated with 4-cholesten-3-one.…”
Section: Discussionmentioning
confidence: 99%
“…Fluvastatin conjugated with human immunodeficiency virus type 1 (HIV-1) trans-activator transcription peptide (TAT) produces anti-proliferative action against human hepatoma cancer cells through a concomitant accumulation of cells in the pre-G phase and induction of caspase 3 cleavage [ 82 ]. Atorvastatin causes strong growth inhibition of epithelial- and mixed epithelial-mesenchymal cancer cells by inhibiting the protein prenylation pathway [ 83 ]. Rosuvastatin inhibits cell proliferation and spheroid formation without cytotoxicity in prostate cancer cells and inhibits the expression of EMT markers vimentin, and Zeb-1 [ 84 ].…”
Section: Statin As a Single Agent In The Suppression Of Cancer Cell Proliferation And The Induction Of Apoptosismentioning
confidence: 99%